DIGITAL ASSESSMENT IN ENGLISH LANGUAGE TEACHING: INNOVATIVE METHODS FOR EVALUATING LANGUAGE COMPETENCE - Gurbanmammedova Govher Nurmuhammedovna; Akmuhammedov Toyli Chariyevich (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
This paper analyzes innovative methods for digital assessment in English language teaching, examining technological tools, pedagogical frameworks, and empirical evidence regarding their effectiveness in evaluating language competence across diverse educational contexts. It examines systematic reviews, empirical studies, and theoretical frameworks addressing digital assessment tools.